PENGARUH PENGGUNAAN PUPUK NPK TERHADAP PRODUKSI PADI ( Oryza sativa L. ) VARIETAS CIHERANG - Endang Sri Wahyuni; Saiful -; Endang W. Pudjiastutik (JURNAL BIOSHELL, 2015)
An experiment that was aimed to determine the best formula of NPK compound fertilizer on paddy rice (Oryza sativa L.) production has been conducted from June till September 2008 at farmland of Jember Lor, District of Jember. The experiment was based on Randomized Complete Block Designed with three NPK formula treatments and three replicates. Each experiment plot was 300 m2, ie in row of 30 m x 10 m. The NPK formula were P1 (200:75:75), P2 (150:100:100), and P3 (250:50:50) kg/ha of Urea:SP-36:KCl respectively. The result shown that formula of 250:50:50 resulting the best grain production and significantly different to others.Keywords: Ciherang variety, NPK formula, paddy rice